Production method of packaging material and package
By introducing a polymer resin composition and an inorganic compound gas barrier layer into the packaging material, the problem of degradation of adhesive strength caused by permeable content is solved, and the protection of the packaging material and the improvement of gas barrier properties are achieved.
Patent Information
- Application Number
- JP2024197577
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-03-22
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2040-03-19
AI Technical Summary
When existing packaging materials pack easily permeable contents, there is a problem of adhesive dissolution and deterioration of adhesive strength, especially when using aluminum foil or inorganic vapor deposition film, the adhesive strength is particularly insufficient.
The adhesive strength is enhanced by forming a gas barrier coating and an adhesive layer on the base layer using a packaging material design containing a polymer resin composition, an inorganic compound gas barrier layer and a metal alkoxide hydrolysate.
It effectively suppresses damage to the packaging material by permeable contents, and maintains the bonding strength and gas barrier properties.
Smart Images

Figure 2025020377000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a packaging material and a package. This application claims priority to Japanese Patent Application No. 2019-055594, filed on March 22, 2019, the contents of which are incorporated by reference. [Background technology]
[0002] For example, packaging materials for packaging solid, powder, and liquid contents such as food, medicine, and toiletries are mainly produced by laminating a heat-sealable film (hereinafter referred to as a sealant layer) such as polyethylene or polypropylene onto various stretched film substrates such as polyester, polyamide, and polypropylene, or onto a metal foil substrate such as aluminum foil, using, for example, a polyurethane-based adhesive, etc. In particular, when gas barrier properties are required for the packaging material, a layer having excellent gas barrier properties such as an inorganic vapor deposition film substrate layer or an ethylene-vinyl alcohol copolymer is provided on the packaging material. The contents to be packaged in the packaging material include various materials, and depending on the characteristics of the contents, they may have various effects on the packaging material.
[0003] For example, Patent Document 1 describes a gas barrier packaging material that can prevent coloring of the packaging material even when a coloring substance is used as the content. This gas barrier packaging material is formed by laminating a base layer, an adhesive layer, a gas barrier layer, an anchor coat layer, and a polyolefin resin layer in this order. The anchor coat layer of this laminate is formed by applying and drying an aqueous dispersion in which a polyolefin copolymer resin containing an unsaturated carboxylic acid or its anhydride in the range of 0.01% by mass to 5% by mass is dispersed to have a number average particle size of 1 μm or less without substantially containing a non-volatile water-imparting auxiliary. Furthermore, the polyolefin resin layer is laminated while performing ozone treatment on the surface of the melt-extruded polyolefin resin that contacts the anchor coat layer.
[0004] For example, Patent Document 2 describes a packaging bag for alcohol-containing materials that can safely seal and package a liquid with an alcohol concentration of 50% by mass or more, or a material impregnated with the liquid. This packaging bag for alcohol-containing materials is formed by laminating a base layer, an adhesive layer, a barrier layer, an anchor coat layer, and a polyolefin resin layer in this order. The barrier layer of this laminate is an aluminum foil, or a vapor-deposited film obtained by vapor-depositing aluminum oxide or silicon oxide onto a base film. The anchor coat layer is formed by applying an aqueous dispersion formed by dispersing a polyolefin polymer resin containing 0.01% by mass to 5% by mass of an unsaturated carboxylic acid or its anhydride to a number average particle size of 1 μm or less and substantially not containing a non-volatile water-imparting auxiliary, followed by heating and drying. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent No. 5359079 [Patent Document 2] Japanese Patent No. 5415670 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the above-mentioned conventional packaging materials and packages have the following problems. The contents to be packaged in the packaging material may include, for example, acidic or alkaline substances, fragrances, surfactants, high boiling point organic solvents, medicinal ingredients, alcohol, volatile substances, etc. Such contents may cause a decrease in the lamination strength of the packaging material laminate or cause the laminate to peel off, and are therefore called highly permeable contents. For example, highly permeable contents pass through packaging materials and swell and dissolve the polyurethane adhesive used for lamination, resulting in a problem of reducing the adhesive function of the polyurethane adhesive. In particular, when a barrier substrate such as aluminum foil or inorganic deposition film substrate is used as part of the packaging material, the adhesive function of the polyurethane adhesive is likely to decrease. The reason for this is believed to be that the highly penetrating contents that pass through the sealant layer are trapped by the barrier substrate and accumulate in the polyurethane-based adhesive. In contrast, the technologies described in Patent Documents 1 and 2 have the characteristic that even with contents containing coloring substances or alcohol, swelling and dissolution do not occur as occurs with urethane adhesives. However, the technologies described in Patent Documents 1 and 2 have limitations on the substrate suitable for obtaining adhesive strength, and the adhesive strength with inorganic vapor deposition film substrates is particularly weak, so that even if swelling and dissolution do not occur, they are not suitable for packaging materials that contain highly permeable contents.
[0007] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a packaging material and a package using an inorganic vapor deposition film substrate, in which even if the contents to be packaged are highly permeable contents, a decrease in laminate strength due to the influence of the highly permeable contents is suppressed. [Means for solving the problem]
[0008] In order to solve the above problems, the packaging material of the first aspect of the present invention comprises a substrate made of a polymer resin composition, a gas barrier vapor deposition layer made of an inorganic compound, a gas barrier coating layer formed using a composition containing at least one compound selected from metal alkoxides, hydrolysates of metal alkoxides, and polymers of metal alkoxides, and a hydroxyl group-containing polymer compound, an adhesive layer formed in contact with the gas barrier coating layer and containing an acid-modified polyolefin resin and a silane coupling agent, and a polyolefin sealant layer, laminated in this order.
[0009] In the packaging material of the first aspect described above, the gas barrier coating layer may be a composition formed by using a composition containing at least one compound selected from metal alkoxides, hydrolysates of metal alkoxides, and polymers of metal alkoxides, and a hydroxyl group-containing polymer compound, and further at least one compound selected from isocyanate derivatives, hydrolysates of isocyanate derivatives, and polymers of isocyanate derivatives.
[0010] In the packaging material of the first aspect, the adhesive layer may contain 0.2 parts by mass or more and 2.0 parts by mass or less of the silane coupling agent per 100 parts by mass of the acid-modified polyolefin resin.
[0011] In the packaging material of the first aspect, the silane coupling agent may be an epoxy-based silane coupling agent.
[0012] In the packaging material of the first aspect described above, the epoxy-based silane coupling agent may be composed of at least one compound selected from the group consisting of 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 3-glycidoxypropyltriethoxysilane.
[0013] In the packaging material of the first aspect, the gas barrier vapor deposition layer may contain at least one of silicon oxide and aluminum oxide.
[0014] In the packaging material of the first aspect, the metal alkoxide may be made of at least one compound selected from the group consisting of tetraethoxysilane, tetramethoxysilane, and triisopropoxyaluminum.
[0015] In the packaging material of the first aspect, the coating amount of the adhesive layer after drying is 0.1 to 2.0 g / m 2 may be also possible.
[0016] The packaging material of the first aspect may further comprise a paper sheet.
[0017] A packaging body according to a second aspect of the present invention comprises a packaging bag formed from the packaging material according to the first aspect, and a highly permeable content contained in the packaging bag and including a highly permeable material.
[0018] Another packaging body of the present invention comprises a liquid paper container formed from the packaging material of the first aspect described above having a paper sheet, and a highly permeable content contained in the liquid paper container, the highly permeable content including a highly permeable material.
[0019] A third aspect of the present invention is a method for producing the packaging material according to the first aspect. In this method, a polyolefin sealant layer is laminated by extrusion lamination at an extrusion temperature of 250°C to 330°C. Effect of the Invention
[0020] According to the packaging material and package of the present invention, even if the content to be packaged is a highly permeable content, it is possible to suppress a decrease in laminate strength caused by the influence of the highly permeable content. [Brief description of the drawings]
[0021] [Figure 1] FIG. 2 is a schematic front view showing an example of a packaging body according to the first embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing an example of a packaging material according to a first embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view of a packaging material according to a second embodiment of the present invention. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a modified example of the packaging material. [Diagram 5] FIG. 2 is a diagram showing an example of a paper container for liquid formed from the same packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] A packaging body and a packaging material according to a first embodiment of the present invention will be described with reference to the accompanying drawings. Fig. 1 is a schematic front view showing an example of a packaging body according to the present embodiment, and Fig. 2 is a schematic cross-sectional view showing an example of a packaging material according to the present embodiment.
[0023] As shown in FIG. 1, a package 3 of this embodiment includes a packaging bag 1 and a highly permeable content 2. In the example shown in Fig. 1, the packaging bag 1 is a flat bag in which a first laminate film 1a and a second laminate film 1b are heat-sealed. The shape of the packaging bag 1 when viewed from the front is, for example, substantially rectangular. In Fig. 1, the first laminate film 1a is disposed on the front side of the figure. The second laminate film 1b has an outer shape similar to that of the first laminate film 1a, and is disposed on the back side of the first laminate film 1a, overlapping with the first laminate film 1a. A spout portion 1d is formed at a corner of the packaging bag 1 to form a flow path for pouring out the highly permeable contents 2 when the packaging bag 1 is opened. The spout portion 1d may be embossed with a line or the like as needed. A pouring pipe (not shown) may be provided inside the spout portion 1d as needed. The spout portion 1d may be provided with a notch for opening, a fragile portion serving as an opening assist line, or the like as needed.
[0024] The package 3 is produced by injecting the highly permeable contents 2 into a bag having a first laminate film 1a and a second laminate film 1b heat-sealed on three sides, and then heat-sealing the opening. However, the type of packaging bag 1 is not limited to a flat bag as long as it can accommodate the highly permeable contents 2 described below. For example, the packaging bag 1 used in the package 3 may be a gusset pouch, a standing pouch, or the like.
[0025] The strong permeability contents 2 in this embodiment are contents containing a suitable strong permeability material. The strong permeability material is a substance that has high permeability into the packaging material. For example, when a highly permeable material is contained inside a packaging bag made of a laminated film, the highly permeable material may permeate from the inner layer to the outer layer of the laminated film. The highly permeable material that has permeated into the laminated film may deteriorate the laminated film. For example, the highly permeable material that has permeated into the laminated film may corrode the film base material of the laminated film or reduce the adhesive strength between the layers of the laminated film. Examples of such highly penetrating materials include acidic substances, alkaline substances, fragrances, surfactants, high boiling point organic solvents, medicinal ingredients, alcohol, and volatile substances.
[0026] However, instead of the highly permeable contents 2, the packaging bag 1 may contain contents that do not contain a highly permeable material. Therefore, examples of contents that can be accommodated in the packaging bag 1 include edible agents, daily necessities, medical agents, industrial agents, reagents, and the like. Examples of edible agents include beverages such as milk, tea, coffee, edible oil, juice, soft drinks, carbonated drinks, and alcohol, as well as cooking agents such as seasonings, edible oils, vinegar, dressings, spice powders, and curry powder. For example, household products include detergents, toothpastes, hair tonics, hair care products, shampoos, rinses, perm solutions, cosmetics, bath additives, fragrances, toiletries, and floor wax. For example, medicinal agents include medicines such as mouthwashes, patches, and disinfectants. For example, industrial agents include reagents, engine oils, motor oils, silicone oils, and the like. For example, the reagents include l-menthol, d-limonene, methyl salicylate, camphor, and the like.
[0027] The first laminate film 1a and the second laminate film 1b each use the laminate film 4, which is the packaging material of this embodiment. As shown in FIG. 2, the laminated film 4 is composed of at least a substrate 4A, a gas barrier deposition layer 4B, a gas barrier coating layer 4C, an adhesive layer 4D, and a polyolefin sealant layer 4E laminated in this order. The laminated film 4 may, if necessary, have layered parts other than the substrate 4A, the gas barrier deposition layer 4B, the gas barrier coating layer 4C, the adhesive layer 4D, and the polyolefin sealant layer 4E. For example, the laminated film 4 may have a surface protection layer for improving surface strength, a printed layer on which an image is formed, a coating layer for improving adhesive strength between layers, and the like.
[0028] The substrate 4A is a film material made of an appropriate polymer resin composition. For example, examples of the polymer resin material that is the main component of the substrate 4A include polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polyolefin resins such as polyethylene and polypropylene, polystyrene resins, polyamide resins such as 6,6-nylon, polycarbonate resins, polyacrylonitrile resins, and polyimide resins. The base material 4A may be a stretched film material or an unstretched film material, but it is particularly preferable to use a biaxially stretched film material as the base material 4A. As the base material 4A, it is more preferable to use a polyamide film, a polyester film, or a polypropylene film from the viewpoints of moisture resistance, suitability for filling, ease of opening, impact resistance, texture, disposability, etc. It is particularly preferable to use a polyester film as the base material 4A.
[0029] Various well-known additives may be contained in the substrate 4A. For example, additives such as a stabilizer, an antistatic agent, a plasticizer, a lubricant, and an antioxidant may be used in the substrate 4A as necessary.
[0030] The thickness of the base material 4A is not particularly limited. From the viewpoint of processability and filling suitability, the thickness of the base material 4A may be 3 μm or more and 200 μm or less. The thickness of the base material 4A is more preferably 6 μm or more and 30 μm or less.
[0031] In order to improve the adhesion between the base material 4A and the gas barrier vapor deposition layer 4B described below, the surface of the base material 4A may be subjected to a pretreatment such as a corona treatment, a plasma treatment, an ozone treatment, etc. Furthermore, the surface of the base material 4A may be subjected to a chemical treatment, a solvent treatment, etc. In particular, it is preferable to subject the base material 4A to a plasma treatment, since the plasma treatment will result in strong adhesion between the gas barrier vapor-deposited layer 4B (described later) and the base material 4A.
[0032] Similarly, a coating layer may be provided to improve adhesion between the substrate 4A and a gas barrier vapor deposition layer 4B described below. Materials for the coating layer include at least one compound selected from the group consisting of organic compounds obtained by the reaction of polyols with isocyanate compounds, organic compounds having a urea bond obtained by the reaction of a polyisocyanate compound with water, polyethyleneimine and its derivatives, polyolefin emulsions, polyimide, melamine, phenol, inorganic silica, and organic silane compounds.
[0033] Examples of polyols include acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol.
[0034] As the isocyanate compound, monomers such as aromatic tolylene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI), and aliphatic xylene diisocyanate (XDI) and hexane diisocyanate (HMDI), as well as polymers and derivatives thereof, can be used alone or in mixtures, and high adhesion to the substrate 4A and gas barrier vapor deposition layer 4B can be obtained by the urethane bond formed by the reaction between the acrylic polyol and the isocyanate compound.
[0035] Examples of inorganic silica include organically modified colloidal silica. The organic silane compound includes a silane coupling agent and a hydrolyzate thereof.
[0036] Particularly preferred materials for the coating layer include a composition containing a trifunctional organosilane represented by the general formula R'Si(OR)3 (R': alkyl group, vinyl group, glycidoxypropyl group, etc., R: alkyl group, etc.) or a hydrolyzate of the trifunctional organosilane, and a composite of an acrylic polyol and an isocyanate compound. Examples of the trifunctional organosilane include ethyltrimethoxysilane, vinyltrimethoxysilane, and glycidoxypropyltrimethoxysilane. Among them, glycidoxytrimethoxysilane and epoxycyclohexylethyltrimethoxysilane containing an epoxy group in R' are particularly preferred because they provide particularly high adhesion between the substrate 4A and the gas barrier deposition layer 4B. The hydrolyzate can be obtained by a known method, such as a method of adding an acid or an alkali to a trifunctional organosilane to perform hydrolysis.
[0037] Various additives, such as curing accelerators, antioxidants, leveling agents, flow control agents, catalysts, crosslinking reaction accelerators, and fillers, can also be added to these coating materials. The thickness of the coating layer is preferably in the range of 0.01 μm to 2.0 μm. If the thickness is thinner than 0.01 μm, it is difficult to obtain a uniform coating film, and adhesion may decrease. If the thickness exceeds 2.0 μm, the coating film cannot maintain flexibility due to its thickness, and there is a risk of cracking of the coating film due to external factors, which is not preferable. It is particularly preferable that the thickness is in the range of 0.05 μm to 0.5 μm. The coating layer can be formed, for example, by a known application method such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, spray coating, etc., or a known printing method such as offset printing, gravure printing, silk screen printing, etc. Drying conditions may be those generally used.
[0038] The gas-barrier vapor-deposited layer 4B is made of an inorganic compound having gas-barrier properties. In the example shown in Fig. 2, the gas-barrier vapor-deposited layer 4B is laminated on a substrate 4A. The inorganic compound may be an oxide, nitride, or fluoride of silicon, aluminum, titanium, zirconium, tin, magnesium, or the like, and may be a single substance or a mixture of a plurality of substances. Aluminum oxide or silicon oxide is particularly preferred for the gas barrier vapor-deposited layer 4B, and since these materials have excellent transparency and water resistance against boiling and retort sterilization treatments while maintaining gas barrier properties, they are suitable for the gas barrier vapor-deposited layer 4B. The degree of oxidation of the vapor-deposited layer of aluminum oxide or silicon oxide need not be limited as long as the gas barrier properties, transparency, etc. are not impaired.
[0039] The thickness of the gas barrier vapor-deposited layer 4B is preferably 5 nm or more and 300 nm or less. If the thickness exceeds 300 nm, the flexibility decreases and cracks may easily occur, so the thickness is more preferably 5 nm or more and 300 nm or less.
[0040] Methods for forming the gas barrier vapor deposition layer 4B include vacuum vapor deposition methods such as resistance heating, induction heating, and EB heating, as well as reactive vapor deposition, reactive sputtering, reactive ion plating, and plasma chemical vapor deposition (CVD), in which a film is formed in the presence of a mixed gas of oxygen, carbon dioxide, and an inert gas.
[0041] The gas barrier coating layer 4C is a layer formed by coating a coating agent prepared by mixing an aqueous solution containing a hydroxyl group-containing polymeric compound or a mixed solution of water and alcohol with at least one selected from a metal alkoxide, or a pre-hydrolyzed metal alkoxide and a polymer of a metal alkoxide, on the gas barrier vapor deposition layer 4B, and then heating and drying the coating agent.
[0042] Examples of the hydroxyl group-containing polymer compound used in the gas barrier coating layer 4C include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, ethylene-vinyl alcohol copolymer, etc. Polyvinyl alcohol (hereinafter referred to as PVA), which has good gas barrier properties, is preferable.
[0043] The metal alkoxide used in the gas barrier coating layer 4C is represented by the general formula: M(OR) n (M: metals such as Si, Ti, Ai, Zr, etc., R: alkyl groups such as CH3, C2H5, etc.). Specific examples include the general formula Si(OR 1 ) 4 [General formula (1)] (wherein R 1 Tetraethoxysilane [Si(OC2H5)4], tetramethoxysilane [Si(OCH3)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc., represented by the formula (wherein represents CH3, C2H5, or C2H4OCH3), are preferred because they are relatively stable in aqueous solvents after hydrolysis. The hydrolysate can be obtained by known methods, such as a method in which an acid, an alkali, etc. is added to a metal alkoxide to carry out hydrolysis.
[0044] The gas barrier coating layer 4C is formed from a coating agent prepared by mixing at least one selected from a metal alkoxide, a hydrolyzed metal alkoxide, and a polymer of a metal alkoxide with an aqueous solution or a mixed solution of water and alcohol containing a hydroxyl group-containing polymeric compound, and the metal alkoxide is a highly reactive inorganic component that undergoes hydrolysis and polycondensation reaction in the solution to form a chain-like or three-dimensional dendritic polymer, and further polymerization proceeds as the solvent evaporates during drying and heating.
[0045] Strong hydrogen bonds are formed between the hydroxyl groups of the hydroxyl group-containing polymeric compound and the hydroxyl groups of the hydrolysate of the metal alkoxide, and when the metal oxide undergoes condensation polymerization, the hydroxyl group-containing polymeric compound disperses among the metal oxides, so that the film structure is similar to a ceramic film, and the gas barrier coating layer 4C itself also exhibits high gas barrier properties.
[0046] In addition, when the gas barrier coating layer 4C is required to have water resistance and heat resistance for boiling sterilization heat treatment, high temperature and high pressure sterilization treatment, etc., a coating agent is prepared by mixing at least one selected from the metal alkoxide, previously hydrolyzed metal alkoxide and polymer of metal alkoxide with an aqueous solution or a mixed solution of water and alcohol containing the hydroxyl group-containing polymer compound, and further mixing the mixture with at least one selected from the metal alkoxide, previously hydrolyzed metal alkoxide and polymer of metal alkoxide, which further comprises a compound represented by the general formula (R 2 Si(OR 3 )3) n [General formula (2)] (wherein, R 2 is an organic functional group, R 3 The silicon compound may be formed by adding and mixing at least one compound selected from a silicon compound represented by the formula (I) (wherein R represents CH3, C2H5, or C2H4OCH3), a hydrolyzate thereof, and a polymer thereof, and then coating and heating and drying the resulting solution.
[0047] The organic functional group R in the general formula (2) 2More preferably, is selected from non-aqueous functional groups such as vinyl, epoxy, methacryloxy, ureido, and isocyanate, etc. The non-aqueous functional groups further improve water resistance because the functional groups are hydrophobic.
[0048] It is preferable that the silicon compound represented by the general formula (2) is a composition formed using at least one compound selected from an isocyanate derivative, a hydrolyzate of an isocyanate derivative, and a polymer of an isocyanate derivative.
[0049] When the silicon compound represented by the general formula (2) is a polymer, it is preferably a trimer. 4 Si(OR 3 )3)3(R in the formula 4 (CH2) n , n is 1 or more). This is a condensation product of 3-isocyanatoalkylalkoxysilane.
[0050] The 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is more preferably 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate, and even more preferably 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate.
[0051] The hydrolyzate can be obtained by a known method, such as a method in which an acid, an alkali or the like is added to the silicon compound represented by the general formula (2) to carry out hydrolysis.
[0052] Although the isocyanurate portion of this 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate loses chemical reactivity, it is known to exhibit the same performance as a reaction due to the polarity of the isocyanurate portion. In general, it is added to adhesives in the same way as 3-isocyanate alkylalkoxysilane, and is known as an adhesion improver. Therefore, 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is a Si(OR1 By adding 4) to the hydroxyl group-containing polymer compound, the gas barrier coating layer 4C can be prevented from swelling with water due to hydrogen bonds, and water resistance can be improved.
[0053] In addition, 3-isocyanate alkyl alkoxy silanes are highly reactive and have low liquid stability, whereas the nurate portion is not water-soluble due to its polarity, but is easily dispersed in aqueous liquids and can maintain stable liquid viscosity, and its water resistance is equivalent to that of 3-isocyanate alkyl alkoxy silanes. Furthermore, the nurate portion is not only water-resistant, but also has a high water resistance due to its polarity, making it possible to form Si(OR 1 )4 Water-soluble polymers containing hydroxyl groups are less likely to form pores in the barrier.
[0054] In addition, the organic functional group R 2 As the organic functional group, a 3-glycidoxypropyl group or a 2-(3,4-epoxycyclohexyl) group can be preferably used. These organic functional groups are converted by hydrolysis into the Si(OR 1 Since hydrogen bonds are formed between the hydroxyl group-containing polymer compound and the methyl group-containing polymer compound, holes are unlikely to form in the barrier, and water resistance can be improved without impairing the gas barrier properties.
[0055] In the above embodiment, the metal element of the metal alkoxide is silicon, but the metal of the metal alkoxide is not limited to silicon. The metal of the metal alkoxide may be, for example, aluminum.
[0056] Furthermore, the gas barrier coating layer 4C may contain known additives such as an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity adjuster, a colorant, etc., within the range that does not impair the barrier properties. For example, the isocyanate compound added to the coating agent may have two or more isocyanate groups (NCO groups) in its molecule. As the isocyanate compound, for example, monomers such as tolylene diisocyanate (hereinafter referred to as TDI), triphenylmethane triisocyanate (hereinafter referred to as TTI), and tetramethylxylene diisocyanate (hereinafter referred to as TMXDI), as well as polymers and derivatives thereof may be used.
[0057] The thickness of the gas barrier coating layer 4C varies depending on the type of coating agent, but may be, for example, in the range of about 0.01 μm to 100 μm after drying. If the thickness is 50 μm or more, the film is likely to crack, so the thickness of the coating after drying is more preferably 0.01 μm to 50 μm.
[0058] Examples of methods that can be used to apply the gas barrier coating agent include well-known application methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, and spray coating, and well-known printing methods such as offset printing, gravure printing, and silk screen printing.
[0059] The gas barrier coating layer 4C is laminated onto the gas barrier vapor deposition layer 4B to fill and reinforce defects or micropores such as pinholes, cracks, and grain boundaries that occur in the gas barrier vapor deposition layer 4B, thereby forming a dense structure, which improves the gas barrier properties and serves as a protective layer for the gas barrier vapor deposition layer 4B. The gas barrier coating layer 4C also has excellent adhesion to the adhesive layer 4D described below.
[0060] The adhesive layer 4D is formed by applying an aqueous medium coating liquid containing an acid-modified polyolefin resin and a silane coupling agent to the gas barrier coating layer 4C, and then heating and drying the coating liquid, and adheres the gas barrier coating layer 4C to the polyolefin sealant layer 4E described below. Here, the aqueous medium refers to water or a mixture of water and an organic solvent.
[0061] The acid-modified polyolefin resin used in the adhesive layer 4D contains an olefin component as a main component and is acid-modified with an unsaturated carboxylic acid component. Examples of the acid-modified polyolefin resin include ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid-maleic anhydride copolymer, ethylene-acrylic acid ester-maleic anhydride copolymer, acid anhydride-modified polyethylene, acid anhydride-modified polypropylene, acid anhydride-modified ethylene-propylene resin, acid anhydride-modified ethylene-butene resin, acid anhydride-modified propylene-butene resin, acid anhydride-modified ethylene-propylene-butene resin, or these acid-modified resins further acrylic-modified with acrylic acid ester, etc. Furthermore, the acid-modified polyolefin resin may be chlorinated in the range of 5% by mass to 40% by mass.
[0062] The type of silane coupling agent contained in the adhesive layer 4D is not particularly limited.For example, the silane coupling agent suitable for the adhesive layer 4D includes epoxy-based silane coupling agent, vinyl-based silane coupling agent, styryl-based silane coupling agent, methacryl-based silane coupling agent, acrylic-based silane coupling agent, amino-based silane coupling agent, isocyanurate-based silane coupling agent, ureido-based silane coupling agent, mercapto-based silane coupling agent, isocyanate-based silane coupling agent, acid anhydride-based silane coupling agent, etc.As the silane coupling agent, it is more preferable to use an epoxy-based silane coupling agent.
[0063] The content of the silane coupling agent in the adhesive layer 4D may be 0.2 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the acid-modified polyolefin resin, more preferably 0.2 parts by mass or more and 1.5 parts by mass or less, and particularly preferably 0.5 parts by mass or more and 1.0 parts by mass or less. If the content of the silane coupling agent is less than 0.2 parts by mass, the adhesion to the gas barrier coating layer 4C and the olefin-based sealant layer may be poor, whereas if the content of the silane coupling agent is more than 2 parts by mass, the liquid stability of the coating liquid may be poor, and the coating liquid may not be uniformly applied to the coating target.
[0064] Examples of compounds that can be used as silane coupling agents include 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane. Among them, it is more preferable to use 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, or 3-glycidoxypropyltriethoxysilane as the silane coupling agent, since it is possible to form an adhesive layer 4D that has excellent adhesion to the gas barrier coating layer 4C and the olefin-based sealant layer.
[0065] The thickness of the adhesive layer 4D (amount of coating after drying) is not particularly limited as long as adhesion is obtained. From the viewpoint of processability, however, it is preferable that the thickness be 0.1 g / m 2 More than 2.0g / m 2 In particular, when laminating by extrusion lamination, it is preferable that the thickness is 0.3 g / m or less from the viewpoint of resistance to contents. 2 More than 1.0g / m 2 It is more preferable that:
[0066] Examples of methods for applying the adhesive layer 4D include well-known application methods such as dipping, roll coating, gravure coating, reverse coating, air knife coating, comma coating, die coating, screen printing, and spray coating, as well as well-known printing methods such as offset printing, gravure printing, and silk screen printing.
[0067] The polyolefin sealant layer 4E is a layer portion for heat-sealing the laminated films 4. The polyolefin sealant layer 4E is formed on the outermost layer of the laminated film 4. Examples of the resin constituting the polyolefin-based sealant layer 4E include polyethylene-based resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HMPE), and ethylene-α-olefin copolymers; polypropylene-based resins such as homopolypropylene resin, propylene-ethylene random copolymer, propylene-ethylene block copolymer resin, and propylene-α-olefin copolymer; and ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymer (EAA) and ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl acrylate, ethylene-ethyl acrylate, ethylene-methacrylic acid copolymer (EMAA), and the like. Examples of the resins that can be used include copolymers with esters of ethylene-α,β-unsaturated carboxylic acid copolymers such as methyl acrylate and ethylene-ethyl methacrylate; ionic crosslinks of ethylene-α,β-unsaturated carboxylic acid copolymers in which the carboxylic acid moieties are crosslinked with sodium ions or zinc ions; modified polyolefin resins obtained by acid-modifying olefin resins such as acid anhydride-modified polyolefins represented by terpolymers such as ethylene-maleic anhydride graft polymers and ethylene-ethyl acrylate-maleic anhydride graft polymers; epoxy compound-modified polyolefins such as ethylene-glycidyl methacrylate copolymers; and ethylene-vinyl acetate copolymers, either alone or in blends of two or more of these resins. The thickness of the polyolefin sealant layer 4E may be appropriately determined depending on, for example, the seal width, required strength, contents, etc. of the heat-sealed portion 1c of the packaging bag 1. For example, the thickness of the polyolefin sealant layer 4E may be 3 μm or more and 200 μm or less.
[0068] Examples of methods for forming the polyolefin sealant layer 4E include a dry lamination method in which a film made of the above-mentioned resin is bonded using a two-component curing urethane adhesive, a non-solvent dry lamination method in which a solvent-free adhesive is used for bonding, and an extrusion lamination method in which the above-mentioned resin is heated and melted, extruded into a curtain shape, and bonded. As a method for forming the polyolefin-based sealant layer 4E, the back lamination method in which the above resin is melt-extruded in a single layer or co-melt-extrusion of two or more types by extrusion lamination, or the sand lamination method in which the resin is melt-extruded on the inside of a polyolefin-based sealant film, are particularly preferred, because they can be thermocompressed to the adhesive layer 4D at high temperatures and have improved adhesion.
[0069] When the polyolefin sealant layer 4E is melt-extruded onto the adhesive layer 4D by the extrusion lamination method, the resin temperature under the T-die is preferably 250° C. to 330° C. If the temperature is below 250° C., the extruded polyolefin resin is insufficiently oxidized, resulting in a decrease in adhesive strength with the adhesive layer 4D. If the temperature is above 330° C., the cohesive force of the extruded resin decreases, resulting in a decrease in adhesive strength with the adhesive layer 4D. Also, the portions where the resin extruded from the T-die contacts the adhesive layer 4D and the vicinity thereof may be subjected to ozone treatment by flowing ozone therethrough, or surface activation treatment such as corona treatment may be performed before bonding.
[0070] The adhesive layer 4D may be formed by a process of applying the adhesive layer 4D to the gas barrier coating layer 4C in advance and drying the same, and in a separate process, the polyolefin sealant layer 4E may be melt-extruded and bonded by an extrusion lamination method or the like. In this way, the process of forming the adhesive layer 4D and the process of melt-extruding and bonding the polyolefin sealant layer 4E may be performed by separate methods. Alternatively, the adhesive layer 4D may be applied onto the gas barrier coating layer 4C, dried, and then the polyolefin sealant layer 4E may be melt-extruded and bonded to the gas barrier coating layer 4C in the same process using a method such as extrusion lamination. If necessary, after the laminate film 4 is formed, it may be heated and pressed by a thermal lamination method to further increase the adhesive strength.
[0071] The substrate 4A may have a buffer layer made of, for example, oriented nylon, oriented polyester, oriented polypropylene, etc., on the surface opposite to the gas barrier deposition layer. When such a buffer layer is provided, the pinhole resistance, impact resistance, heat resistance, etc. of the laminated film 4 are improved.
[0072] The laminated film 4 is formed by laminating the above-described substrate 4A, gas barrier deposition layer 4B, gas barrier coating layer 4C, adhesive layer 4D, and polyolefin sealant layer 4E in this order. However, when other layered parts are provided as necessary, they are laminated in this order with the other layered parts sandwiched therebetween. The order of formation of each layered part and the formation unit are not particularly limited. To manufacture the packaging bag 1, the laminate film 4 is first cut to have the outer shapes of the first laminate film 1a and the second laminate film 1b, respectively. Furthermore, the first laminate film 1a and the second laminate film 1b are laminated so that the polyolefin sealant layers 4E of the first laminate film 1a and the second laminate film 1b face each other. The laminate of the first laminate film 1a and the second laminate film 1b is heat-sealed on three outer peripheries by a heat-sealing device. This produces a packaging bag 1 that is open on one side. If a fragile part such as an opening assist line is provided at the spout part 1d of the packaging bag 1, the fragile part is formed at some point before the packaging bag 1 is formed. For example, laser processing or the like may be used to process the fragile part.
[0073] After the packaging bag 1 is manufactured, the highly permeable content 2 is filled in through the opening. After that, the opening of the packaging bag 1 is heat-sealed by a heat-sealing device. In this way, a heat-sealed portion 1c is formed around the entire outer periphery of the packaging bag 1. As a result, the packaging bag 1 is sealed and the package 3 is manufactured.
[0074] Next, the functions of the laminated film 4 and the packaging bag 1 of this embodiment will be described. As described above, the laminated film 4 includes a gas barrier deposition layer 4B, a gas barrier coating layer 4C, and an adhesive layer 4D, each of which has gas barrier properties, between a substrate 4A and a polyolefin sealant layer 4E. The gas barrier properties of the gas barrier vapor-deposited layer 4B are achieved by the inorganic compound contained in the gas barrier vapor-deposited layer 4B forming a dense layer structure. Such an inorganic compound layer is hard but brittle, and therefore is prone to cracks when an external force is applied, such as when the laminate film 4 is bent. The cracks can cause a decrease in the gas barrier properties. In this embodiment, the gas barrier vapor deposition layer 4B is further covered with a gas barrier coating layer 4C.
[0075] In the gas barrier coating layer 4C, for example, a silicon compound of general formula (1) is hydrolyzed, and strong hydrogen bonds are formed between the hydroxyl groups of the hydrolyzate of the silicon compound and the hydroxyl groups of the hydroxyl group-containing polymer compound. Therefore, in the gas barrier coating layer 4C, a flexible hydroxyl group-containing polymer compound is dispersed in a dense network of the silicon compound. The hydroxyl group-containing polymer compound bonds to sites derived from the arrangement of functional groups of the silicon compound of general formula (1), and is dispersed evenly over a wide area. As a result, holes through which gas can easily pass as described above are unlikely to be formed inside the membrane structure. In this way, the gas barrier deposition layer 4B is coated with the gas barrier coating layer 4C which has both gas barrier properties and flexibility, and thus the gas barrier properties of the laminate film 4 are further improved by a synergistic effect. In this way, the laminated film 4 suppresses the permeation of highly permeable materials.
[0076] Furthermore, in the gas barrier coating layer 4C, strong hydrogen bonds are formed between the hydroxyl group produced by hydrolysis of the silicon compound of general formula (2), the hydroxyl group of the hydrolyzate of the silicon compound of general formula (1), and the hydroxyl group of the hydroxyl-containing polymer compound. On the other hand, the hydrophobic organic functional group of general formula (2) forms a network, which prevents swelling even when water is added to the hydrogen bonds of the hydroxyl-containing polymer compound. This significantly improves the water resistance of the film structure.
[0077] Furthermore, in this embodiment, in the adhesive portion between the gas barrier coating layer 4C and the adhesive layer 4D, the highly polar silanol groups generated by hydrolysis of the silicon compounds contained in the general formulas (1) and (2) in the gas barrier coating layer 4C create a strong bond by interaction with the highly polar epoxy groups of the epoxy-based silane coupling agent in the adhesive layer 4D. This allows the gas barrier coating layer 4C and the adhesive layer 4D to maintain their mutual adhesive force even if the highly permeable substance of the highly permeable contents reaches them. In addition, the highly polar hydroxyl group of the hydroxyl group-containing polymer compound in the gas barrier coating layer 4C creates a strong bond through interaction with the highly polar epoxy group of the epoxy-based silane coupling agent in the adhesive layer 4D. This allows the gas barrier coating layer 4C and the adhesive layer 4D to maintain their mutual adhesive force even if the highly permeable substance of the highly permeable contents reaches them.
[0078] Furthermore, since the polyolefin resin component of the acid-modified polyolefin resin in the adhesive layer 4D and the polyolefin resin in the polyolefin-based sealant layer 4E are of the same resin system, strong adhesive strength is created, and the adhesive layer 4D and the polyolefin-based sealant layer 4E can maintain their adhesive strength even if a highly permeable substance from the highly permeable contents reaches them.
[0079] As described above, according to the packaging material and package of the present embodiment, even if the contents to be packaged are highly permeable contents, the decrease in laminate strength caused by the influence of the highly permeable contents is suppressed. EXAMPLES
[0080] Examples 1 to 8 of the laminated film 4 and packaging body 3 of the above embodiment will be described below along with Comparative Examples 1 to 5. The layer structures of the packaging materials, the types of contents, and the evaluation results in Examples 1 to 8 and Comparative Examples 1 to 5 are shown in [Table 1] below. However, the reference numerals of each layer are omitted in [Table 1].
[0081] [Table 1]
[0082] The compositions of Compositions A to E in [Table 1] are shown in the following [Table 2].
[0083] [Table 2]
[0084] [Example 1] As shown in Table 1, as the base material 4A of the packaging material of Example 1, a 12 μm-thick polyethylene terephthalate film ("PET" in Table 1) that had no surface treatment was used. Aluminum oxide was used as the gas barrier vapor-deposited layer 4B. The aluminum oxide was formed on the substrate 4A by vacuum deposition to a thickness of 15 nm. The ratio B / A of aluminum (B) to oxygen (A) in the gas barrier vapor-deposited layer 4B was measured by XPS (X-ray Photoelectron Spectroscopy) and found to be B / A=1 / 1.8. Composition a was used as the material for the gas barrier coating layer 4C. Composition a contained tetraethoxysilane (Si(OC2H5)4, hereinafter referred to as TEOS), which is a metal alkoxide, or pre-hydrolyzed TEOS, and a polymer of these, and PVA, which is a polymer compound having a hydroxyl group.
[0085] A coating solution described below was applied to the upper surface of the gas barrier vapor-deposited layer 4B made of aluminum oxide using a bar coater. The coating solution used was a mixture of coating solutions (a) and (b) (gas barrier coating solution) prepared by the following method. The mixing ratio of the coating solutions (a) and (b) was a:b=70:30, where a and b are the masses of the solid contents of each solution. The coating solution (a) was obtained by adding 17.9 g of TEOS and 72.1 g of hydrochloric acid (0.1N) to 10.0 g of methanol, stirring for 30 minutes, and hydrolysis. The solid content of the hydrolysis solution was 5% (weight ratio calculated as SiO2). As the coating solution (b), an aqueous solution of 5% (mass ratio) polyvinyl alcohol and water / methanol=95 / 5 (mass ratio) was obtained. After the mixture was applied, the coating was dried in a dryer at 120° C. for 1 minute, thereby forming a gas barrier coating layer 4C having a thickness of about 0.3 μm.
[0086] Composition A was used as the material for adhesive layer 4D. As shown in Table 2, composition A was prepared as an aqueous dispersion in which 1 part by mass of 3-glycidoxypropyltrimethoxysilane, an epoxy-based silane coupling agent, was added to 100 parts by mass of acid anhydride-modified polyethylene resin. The adhesive layer 4D is applied onto the gas barrier coating layer 4C by a bar coating method, and the coating film is dried in a dryer at 120° C. for 1 minute to give a coating amount of 0.5 g / m 2 The film was formed so that A low-density polyethylene (LDPE) having a thickness of 20 μm was used as the polyolefin-based sealant layer 4E (referred to as the "sealant layer" in [Table 1]). The polyolefin-based sealant layer 4E was laminated on the adhesive layer 4D by extrusion lamination at a temperature of 290°C. In this manner, laminate film 4 of Example 1 was produced.
[0087] The laminated film 4 of Example 1 was cut into the shape of the first laminated film 1a and the second laminated film 1b, and then the three sides of the outer periphery were heat-sealed to form a packaging bag 1. The packaging bag 1 was filled with highly permeable contents α (referred to as "contents α" in Table 1) containing a highly permeable material from the opening. As the strong penetrating ingredient α, l-menthol was used. After the highly permeable content α was filled, the opening of the packaging bag 1 was heat-sealed, thereby producing the packaging body 3 of Example 1 having a bag shape sealed on all four sides.
[0088] [Examples 2 to 8] (packaging material) As shown in Table 1, the laminated film 4 of Example 2 was configured in the same manner as the laminated film 4 of Example 1, except that composition B was used instead of composition A as the adhesive layer 4D. As shown in Table 2, composition B was composed in the same manner as composition A, except that the amount of 3-glycidoxypropyltrimethoxysilane in composition A was changed to 0.5 parts by mass. As shown in Table 1, the laminated film 4 of Example 3 was configured in the same manner as the laminated film 4 of Example 1, except that the composition C was used instead of the composition A as the adhesive layer 4D. As shown in Table 2, composition C had the same composition as composition A, except that 3-glycidoxypropylmethyldimethoxysilane was used instead of 3-glycidoxypropyltrimethoxysilane.
[0089] As shown in Table 1, the laminate film 4 of Example 4 was constructed in the same manner as the laminate film 4 of Example 1, except that the material of the gas barrier vapor-deposited layer 4B was changed from aluminum oxide to silicon oxide. The abundance ratio B / A of oxygen (B) to silicon (A) in the silicon oxide was 1.5.
[0090] The laminate film 4 of Example 5 was constructed in the same manner as the laminate film 4 of Example 1, except that a coating layer was formed on the surface of the substrate 4A, and then the gas barrier vapor deposition layer 4B was formed in order to improve the adhesion of the gas barrier vapor deposition layer 4B. The material used for the coating layer was a solution prepared by adding acrylic polyol and triisocyanate so that the amount of NCO groups was equal to the amount of OH groups in the acrylic polyol, diluting with ethyl acetate so that the total solids content was 5% by mass, and adding and mixing β-(3,4-epoxycyclohexyl)trimethoxysilane at 5% by mass relative to the total solids content. The above mixed solution was applied to the gas barrier vapor deposition layer 4B with a bar coater, and dried in a dryer at 120° C. for 1 minute to obtain a coating layer with a thickness of about 0.3 μm.
[0091] The laminate film 4 of Example 6 was constructed in the same manner as the laminate film 4 of Example 1, except that the surface of the substrate 4A was subjected to oxygen plasma treatment and then the gas barrier vapor deposition layer 4B was formed in order to improve the adhesion of the gas barrier vapor deposition layer 4B.
[0092] The laminate film 4 of Example 7 was configured in the same manner as the laminate film 4 of Example 1, except that the composition b was used as the material for the gas barrier coating layer 4C. Composition b was formed using a gas barrier coating solution in which the coating solution solutions (a) and (b) explained in Example 1 were mixed with the coating solution solution (c) described below. The coating solution (c) was prepared by dissolving 1,3,5-tris(3-methoxysilylpropyl)isocyanurate in a water / IPA=1 / 1 solution with a solid content of 5% (weight ratio R 2 A solution diluted and adjusted to 100% NaCl (equivalent to Si(OH)3) was used. The mixing ratio of the coating solutions (a), (b), and (c) was A:B:C = 100:20:10, where A is the solid content (converted value) of TEOS SiO2, B is the solid content of PVA, and C is the R of 1,3,5-tris(3-methoxysilylpropyl)isocyanurate. 2 The solid content (converted value) is Si(OH)3. Composition b was formed into a film using this coating liquid in the same manner as the gas barrier coating layer of composition a.
[0093] The laminate film 4 of Example 8 was constructed in the same manner as the laminate film 4 of Example 7, except that in order to improve the adhesion of the gas barrier vapor deposition layer 4B, a coating layer was formed on the surface of the substrate 4A in the same manner as in Example 5, and then the gas barrier vapor deposition layer 4B was formed.
[0094] (packaging) The packages 3 of Examples 2-8 were produced in the same manner as the package 3 of Example 1, except that the package bag 1 was produced from the laminate film 4 of Examples 2-8.
[0095] [Comparative Examples 1 to 8] (packaging material) The laminated films of Comparative Examples 1 and 2 were constructed in the same manner as the laminated film 4 of Example 1, except that compositions D and E were used in place of composition A in the adhesive layer 4D. The coating amount of the adhesive layer in each of Comparative Examples 1 and 2 after drying was 0.5 g / m 2 It was stated that. As shown in Table 2, composition D was a two-component curing polyester polyurethane resin. The solid content of composition D was 30% by mass, and the coating amount of composition D after drying was 0.5 g / m 2 After coating using a bar coater so that the coating solution was in the range of 1:100 to 1:100, the coating solution was dried at 120° C. for 1 minute. As a result, an adhesive layer of Comparative Example 1 was formed. Composition E was composed of an acid-modified polyethylene resin that did not contain a silane coupling agent. The acid-modified polyethylene resin was made of the same material as that of composition A.
[0096] As shown in Table 1, the laminate films of Comparative Examples 3 and 4 were constructed in the same manner as Examples 1 and 4, respectively, except that they did not have a gas barrier coating layer. The laminate film of Comparative Example 5 was configured in the same manner as the laminate film 4 of Example 1, except that the composition c was used as the material for the gas barrier coating layer. Composition c was used as an overcoat, a polyester-based aqueous emulsion. The solid content of composition c was 30 mass%. Composition c was applied using a bar coater so that the film thickness after drying was 0.3 μm, and then dried at 120° C. for 1 minute. As a result, a non-gas barrier coating layer of Comparative Example 5 was formed. The laminated film of Comparative Example 6 had a coating amount of the adhesive layer after drying of 2.5 g / m 2 Except for the above, the laminated film was constructed in the same manner as the laminated film 4 of Example 1. The laminated film of Comparative Example 7 was constructed in the same manner as the laminated film 4 of Example 1, except that the temperature during extrusion lamination was 240°C. The laminated film of Comparative Example 8 was constructed in the same manner as the laminated film 4 of Example 1, except that the temperature during extrusion lamination was 350°C.
[0097] (packaging) The packages of Comparative Examples 1 to 8 were produced in the same manner as the package 3 of Example 1, except that a package bag similar to the package bag 1 was produced using the laminated films of Comparative Examples 1 to 8.
[0098] [evaluation] For the evaluation of each Example and Comparative Example, each packaging bag was stored at 40°C and 90% humidity for one month, and then opened. The presence or absence of deterioration of the laminate film of the opened packaging bag, which was thought to have occurred due to the influence of the contents, was examined. Specifically, the lamination strength and water vapor barrier property of the laminate film were examined. The evaluation was made on a three-point scale: good (marked as "○" in Table 1), bad (marked as "△" in Table 1), and very bad (marked as "×" in Table 1). The laminate strength was measured based on JIS Z 1707. The details of each stage are as follows: "Good": 5N / 15mm or more "Poor": Range between "Good" and "Very Poor" "Very bad": 2N / 15mm or less The water vapor barrier property was measured based on JIS Z7129. The details of each stage are as follows. "Good": 0.5g / m 2 / day or less "Poor": Range between "Good" and "Very Poor" "Very bad": 1.0g / m 2 / day or more
[0099] [Evaluation Results] As shown in Table 1, Examples 1 to 8 were evaluated as "good" in both laminate strength and water vapor barrier property. In contrast, in Comparative Examples 3 and 4, elongation of the LDPE extrusion laminate resin, which is thought to be due to the laminate strength, was observed, and both the laminate strength and the water vapor barrier property were evaluated as "poor." In Comparative Examples 1, 2, 5, 6, and 7, interlayer delamination occurred, and the laminate strength was evaluated as "very poor." In Comparative Example 8, the resin, which had become highly fluid due to high-temperature extrusion, destroyed the vapor-deposited gas barrier layer, and the water vapor barrier property was evaluated as "very poor." From the above results, it can be seen that in Examples 1 to 8, even when the contents to be packaged were highly permeable, the decrease in laminate strength due to the influence of the highly permeable contents was suppressed, and the water vapor barrier property was also maintained.
[0100] A second embodiment of the present invention will be described with reference to Figures 3 to 5. In the following description, configurations common to those already described will be given the same reference numerals and duplicated description will be omitted.
[0101] 3 is a schematic cross-sectional view of a packaging material 50 according to this embodiment. The packaging material 50 has a configuration in which the laminated film 4 of the first embodiment and a paper sheet 10 are joined together.
[0102] The paper constituting the sheet 10 has a basis weight of 200 to 500 g / m2 depending on the size of the paper container to be formed. 2 , density 0.6~1.1g / cm 3 The basis weight is 200 g / m2 and can be selected from the range of 200 g / m2. 2 If it is less than 500g / m, it may not be possible to obtain sufficient stiffness or strength for use as a container. 2 If it exceeds this value, the processability when molding into a container will be poor, and it is not economically preferable.
[0103] A surface resin layer 12 is formed on one surface of the sheet. The surface resin layer 12 constitutes the outer surface of the paper container for liquids described below, and is formed of a polyolefin resin. The thickness of the surface resin layer 12 can be, for example, about 10 to 50 μm. The surface resin layer 12 can be formed by an extrusion lamination method.
[0104] The polyolefin sealant layer 4E of the laminated film 4 shown in Fig. 3 includes a polyolefin resin layer 41 and a polyolefin resin sealant film 42, and is formed by the above-mentioned extrusion lamination sand lamination method or back lamination method. The thickness of the polyolefin sealant layer 4E can be, for example, about 40 to 100 µm. This is one example, and the configuration of the polyolefin sealant layer 4E may be any of the aspects described in the first embodiment.
[0105] The laminated film 4 is disposed with the base material 4A side facing the sheet 10. The laminated film 4 and the sheet 10 are bonded together by a bonding resin layer 11 on the surface opposite to the surface resin layer 12. The bonding resin layer 11 can be formed of a polyolefin resin. The thickness of the bonding resin layer 11 can be, for example, about 10 to 50 μm. The bonding resin layer 11 can be formed by an extrusion lamination method.
[0106] Specific examples of resins forming the surface resin layer 12, the bonding resin layer 11, and the polyolefin resin layer 41 include polyethylene resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HMPE), and ethylene-α-olefin copolymers; polypropylene resins such as homopolypropylene resin, propylene-ethylene random copolymer, propylene-ethylene block copolymer resin, and propylene-α-olefin copolymer; and ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymer (EAA) and ethylene-methacrylic acid copolymer (EMAA), ethylene-methyl acrylate, ethylene-ethyl acrylate, ethylene-propylene copolymer, and propylene-propylene copolymer. Examples of resins that can be used include copolymers with esters of ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-methyl methacrylate and ethylene-ethyl methacrylate; ionic crosslinks of ethylene-α,β-unsaturated carboxylic acid copolymers in which the carboxylic acid moieties are crosslinked with sodium ions or zinc ions; modified polyolefin resins obtained by acid-modifying olefin resins such as acid anhydride-modified polyolefins, such as ethylene-maleic anhydride graft polymers and terpolymers such as ethylene-ethyl acrylate-maleic anhydride, by graft polymerization or the like; epoxy compound-modified polyolefins, such as ethylene-glycidyl methacrylate copolymers; and ethylene-vinyl acetate copolymers, either alone or in blends of two or more of these resins. The above resins may be melt-extruded in a single layer or in a co-melt extrusion of two or more types. The resin temperature under the T-die during melt extrusion by the extrusion lamination method is preferably 250° C. to 330° C. If the temperature is below 250° C., the interlayer adhesive strength decreases due to insufficient oxidation of the extruded polyolefin resin. If the temperature is above 330° C., the cohesive force of the extruded resin decreases, resulting in a decrease in the interlayer adhesive strength. Also, the resin extruded from the T-die and its vicinity can be subjected to ozone treatment by flowing ozone therethrough, or surface activation treatment such as corona treatment can be performed before bonding. Since the bonding resin layer 11 is in contact with the base material 4A, among the above, it is preferable to use a single layer or two or more layers of co-melt extrusion of a resin selected from ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymer (EAA) and ethylene-methacrylic acid copolymer (EMAA), copolymers with esters of ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-methyl acrylate, ethylene-ethyl acrylate, ethylene-methyl methacrylate, and ethylene-ethyl methacrylate, ion-crosslinked products of ethylene-α,β-unsaturated carboxylic acid copolymers in which the carboxylic acid moieties are crosslinked with sodium ions or zinc ions, modified polyolefin resins obtained by acid-modifying olefin resins such as acid anhydride-modified polyolefins represented by ethylene-maleic anhydride graft polymers and terpolymers such as ethylene-ethyl acrylate-maleic anhydride graft polymers, epoxy compound-modified polyolefins such as ethylene-glycidyl methacrylate copolymers, and ethylene-vinyl acetate copolymers, or a single layer or a blend of two or more types of resins selected therefrom.
[0107] The packaging material 50 can be produced by preparing a sheet 10 having a surface resin layer 12 formed thereon and a laminate film 4, and bonding the sheet 10 and the laminate film 4 together while forming a bonding resin layer 11 by extrusion lamination. If necessary, after the sheet 10 and the laminated film 4 are joined together, they may be heated and pressed by a thermal lamination method to further increase the adhesive strength.
[0108] Another example of the packaging material is shown in Fig. 4. In the packaging material 50A shown in the figure, the laminated film 4 and the sheet 10 are joined by the polyolefin-based sealant layer 4E of the laminated film 4. On the surface of the substrate 4A that does not face the sheet 10, a container sealant layer 13 having a polyolefin resin layer 13A and a polyolefin resin-based sealant film 13B is formed by a sand lamination method of extrusion lamination. The materials of the polyolefin resin layer 13A and the polyolefin resin-based sealant film 13B can be the same as those of the polyolefin resin layer 41 and the polyolefin resin-based sealant film 42 in the packaging material 50. In this case, since the polyolefin resin layer 41 is in contact with the base material 4A, like the bonding resin layer 11, it is preferable to use a single layer or two or more layers of co-melt extrusion of a resin selected from ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-acrylic acid copolymer (EAA) and ethylene-methacrylic acid copolymer (EMAA), copolymers with esters of ethylene-α,β-unsaturated carboxylic acid copolymers such as ethylene-methyl acrylate, ethylene-ethyl acrylate, ethylene-methyl methacrylate, and ethylene-ethyl methacrylate, ion-crosslinked products of ethylene-α,β-unsaturated carboxylic acid copolymers in which the carboxylic acid moieties are crosslinked with sodium ions or zinc ions, modified polyolefin resins obtained by acid-modifying olefin resins such as acid anhydride-modified polyolefins represented by terpolymers such as ethylene-maleic anhydride graft polymers and ethylene-ethyl acrylate-maleic anhydride graft polymers, epoxy compound-modified polyolefins such as ethylene-glycidyl methacrylate copolymers, and ethylene-vinyl acetate copolymers, or a single layer or a blend of two or more types of resins selected therefrom.
[0109] When producing the packaging material 50A, a portion of the laminate film 4 excluding the polyolefin sealant layer 4E is prepared. After forming the container sealant layer 13 on the laminate film 4 by a sand lamination method of extrusion lamination, the polyolefin sealant layer 4E is formed by a sand lamination method of extrusion lamination, and the sheet 10 on which the surface resin layer 12 is formed is joined to the laminate film 4, thereby producing the packaging material 50A. At this time, the adhesive layer 4D may be formed and dried in advance, or may be formed in the same process in which the polyolefin-based sealant layer 4E is formed by the extrusion lamination method. If necessary, after the sheet 10 and the laminated film 4 are joined together, they may be heated and pressed by a thermal lamination method to further increase the adhesive strength.
[0110] The packaging material 50 or 50A can be made into a blank for a paper container for liquid by forming fold lines by pressing or the like and punching it into a predetermined shape. The blank is folded along the fold lines, assembled, and the necessary parts are heat-sealed to produce a paper container for liquid made of the packaging material of this embodiment. The paper container for liquid according to the present embodiment is manufactured using the laminated film 4, and therefore has good laminate strength between the gas barrier deposition layer 4B and the gas barrier coating layer 4C and the polyolefin sealant layer 4E. Therefore, even if the container is filled with volatile substances or various highly permeable contents containing volatile substances, such as perm solution, detergent, concentrated detergent, shampoo, rinse, bath additives, and aromatics, the laminate strength between the gas barrier deposition layer 4B and the gas barrier coating layer 4C and the polyolefin sealant layer 4E does not decrease, and the container can be suitably used as a paper container for liquids with a large weight or a paper container for liquids for long-term storage. In addition, the container has excellent barrier properties against water vapor and the like.
[0111] Fig. 5 shows a Gabeltop-type paper container 100 for liquids as an example of a paper container for liquids using the packaging material 50. When manufacturing the paper container 100 for liquids, the blank described above is folded to create a cylindrical body. Next, a bottom is formed to create a bottomed container. This bottomed container is filled with contents, and the top opening is folded and sealed to form a top surface. This completes the paper container 100 for liquids (package) filled and sealed with the contents.
[0112] The shape of the paper container for liquid is not limited to the Gabeltop type described above, but may be a flat-top type with the top folded flat, or any other suitable shape. In this embodiment, a part of the surface resin layer 12 is joined by heat fusion to the polyolefin sealant layer 4E or the container sealant layer 13 when the liquid paper container is produced. Therefore, the material of the surface resin layer 12 is preferably one that can be heat fused to the corresponding polyolefin sealant layer 4E or container sealant layer 13. A low crystalline rubber component may be blended into the surface resin layer 12 and the polyolefin-based sealant layer 4E.
[0113] In this embodiment, the container sealant layer 13 and the polyolefin sealant layer 4E (the innermost layer when these layers are composed of a plurality of layers) which form the inner surface of the liquid paper container are preferably formed of polyolefin polymerized using a single-site catalyst such as a metallocene catalyst (metallocene polyolefin). It is known that structural characteristics such as molecular weight, molecular weight distribution, and branched structure of ethylene-based polymers and propylene-based polymers can be controlled by selecting a catalyst, and a person skilled in the art can distinguish the type of polymer depending on the type of catalyst. Polyolefins using a single-site catalyst have a uniform molecular weight distribution, and therefore can stabilize the seal strength.
[0114] The second embodiment will be further described below using examples and comparative examples. The layer structures and evaluation results of the laminated films in the packaging materials of Examples 9 and 10 and Comparative Examples 9 and 10 are shown in Table 3 below.
[0115] [Table 3]
[0116] Example 9 A laminated film similar to that of Example 1 was prepared, except that an ethylene-α-olefin copolymer polymerized using a metallocene catalyst was used as the sealant layer. Sheet 10, basis weight 400 g / m 2 A surface resin layer 12 made of LDPE and having a thickness of 20 μm was formed on one surface of the sheet 10 by extrusion lamination. The base material of the laminated film was placed opposite the surface of the sheet 10 on which the surface resin layer 12 was not provided, and the laminated film and the sheet were bonded together by extrusion lamination (extrusion temperature 290°C) using an ethylene-unsaturated carboxylic acid copolymer. In this way, the packaging material of Example 9 having a bonding resin layer 11 with a thickness of 20 μm was produced.
[0117] Example 10 A laminate film similar to that of Example 8 was prepared, except that an ethylene-α-olefin copolymer polymerized using a metallocene catalyst was used as the sealant layer. This laminate film was attached to a sheet 10 in the same manner as in Example 9, to produce a packaging material of Example 10.
[0118] Comparative Example 9 A laminated film similar to that of Comparative Example 1 was prepared, except that an ethylene-α-olefin copolymer polymerized using a metallocene catalyst was used as the sealant layer. This laminated film was attached to the sheet 10 in the same manner as in Example 9, to produce the packaging material of Comparative Example 9. Comparative Example 10 A laminate film similar to that of Comparative Example 2 was prepared, except that an ethylene-α-olefin copolymer polymerized using a metallocene catalyst was used as the sealant layer. This laminate film was attached to a sheet 10 in the same manner as in Example 9 to produce a packaging material of Comparative Example 10.
[0119] The packaging materials of each Example and Comparative Example were punched out into a predetermined shape to prepare blanks, and the Goebel-top type paper containers for liquids of each Example were prepared. These were filled with the above-mentioned content α and sealed to prepare packages of each Example. The lamination strength and water vapor barrier property of each example of the packaging bag were evaluated in the same manner as in the examples according to the first embodiment.
[0120] As shown in Table 3, Examples 9 and 10 were evaluated as "good" in both laminate strength and water vapor barrier property. In contrast, in Comparative Examples 9 and 10, interlayer delamination occurred, and the laminate strength was evaluated as "very poor." From the above results, it can be seen that in the liquid paper container of the second embodiment, even if the contents to be packaged are highly permeable contents, the decrease in laminate strength due to the influence of the highly permeable contents is suppressed, and the water vapor barrier properties are maintained.
[0121] Although the preferred embodiment and examples of the present invention have been described above, the present invention is not limited to these embodiments and examples. Addition, omission, substitution, and other modifications of the configuration are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited by the foregoing description, but only by the scope of the appended claims. [Industrial Applicability]
[0122] The present invention is applicable to packaging materials and packages. [Explanation of symbols]
[0123] 1 packaging bag 1a First laminated film 1b Second laminated film 1c Heat seal section 1d Spout 2 Highly permeable contents 3 Packaging 4. Laminated film (packaging material) 4A Base material 4B Gas barrier deposition layer 4C Gas barrier coating layer 4D adhesive layer 4E Polyolefin sealant layer 10 Sheets 50, 50A packaging material 100 Liquid cartons
Claims
1. A gas barrier vapor deposition layer made of an inorganic compound is formed on a substrate made of a polymer resin composition; forming a gas barrier coating layer on the gas barrier deposition layer using a composition containing at least one compound selected from a metal alkoxide, a hydrolysate of a metal alkoxide, and a polymer of a metal alkoxide, and a hydroxyl group-containing polymer compound; An aqueous medium coating liquid containing an acid-modified polyolefin resin and a silane coupling agent is applied onto the gas barrier coating layer, and the coating liquid is dried by heating to form an adhesive layer; A polyolefin sealant layer is laminated on the adhesive layer by an extrusion lamination method at an extrusion temperature of 250° C. to 330° C.; The adhesive layer has a coating amount of 0.1 to 2.0 g / m after drying. 2 That is, A method for manufacturing packaging materials.
2. The gas barrier coating layer is A composition formed by using a composition containing at least one compound selected from a metal alkoxide, a hydrolysate of a metal alkoxide, and a polymer of a metal alkoxide, and a hydroxyl group-containing polymer compound, and further at least one compound selected from an isocyanate derivative, a hydrolysate of an isocyanate derivative, and a polymer of an isocyanate derivative. A method for producing the packaging material according to claim 1.
3. The adhesive layer is The silane coupling agent is 0.2 parts by mass or more and 2.0 parts by mass or less per 100 parts by mass of the acid-modified polyolefin resin. A method for producing the packaging material according to claim 1 or 2.
4. The silane coupling agent is It is an epoxy-based silane coupling agent. A method for producing the packaging material according to any one of claims 1 to 3.
5. The epoxy-based silane coupling agent is At least one compound selected from the group consisting of 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 3-glycidoxypropyltriethoxysilane; A method for producing the packaging material according to claim 4.
6. The gas barrier deposition layer is Contains at least one of silicon oxide and aluminum oxide; A method for producing the packaging material according to any one of claims 1 to 5.
7. The metal alkoxide is At least one compound selected from the group consisting of tetraethoxysilane, tetramethoxysilane, and triisopropoxyaluminum, A method for producing the packaging material according to any one of claims 1 to 6.
8. A packaging bag formed using a packaging material manufactured by the manufacturing method according to any one of claims 1 to 7; A highly permeable content contained in the packaging bag and including a highly permeable material; Equipped with packaging.
9. Further joining of the paper sheets, A method for producing the packaging material according to any one of claims 1 to 7.
10. A liquid paper container formed using a packaging material manufactured by the manufacturing method according to claim 9; A highly permeable content that is contained in the liquid paper container and includes a highly permeable material; Equipped with packaging.
Citation Information
Patent Citations
Barrier laminate, packaging material using the same, and packed body using the same
JP2000025145A
Packaging material
JP2008229971A
Gas barrier film and method of manufacturing the same
JP2012223919A
Paper container for liquid
JP2013095501A
Gas barrier laminate film
JP2013202822A